Correlations Between Interleukin-11 Expression and Hypertensive Kidney Injury in a Rat Model of Renovascular Hypertension - Menendez-Castro, Carlos; Cordasic, Nada; Dambietz, Thomas; Veelken, Roland; Amann, Kerstin Ute; Hartner, Andrea; Hilgers, Karl Friedrich (American Journal of Hypertension, 2020)
BACKGROUND: Interleukin-11 (IL-11) is a pleiotropic cytokine of the interleukin-6 family. Recent studies revealed its crucial role in the development of cardiovascular fibrosis. In this study we examined IL-11 expression levels in the heart and the kidney exposed to high blood pressure in renovascular hypertensive rats and their correlations to fibrotic markers and kidney injury. METHODS: Two-kidney, one-clip renovascular hypertension (2K1C) was induced in rats. IL-11 expression was measured by real-time polymerase chain reaction in the left ventricle and the right kidney. The correlation of cardiac IL-11 expression with biomarkers of renal fibrosis was assessed. We further investigated IL-11 expression in 2K1C rats grouped into rats with malignant vs. nonmalignant hypertension (distinguishing criteria: weight loss, number of fibrinoid necrosis, and onion skin lesions). RESULTS: Thirty-five days after clipping, mean arterial pressure was significantly increased in 2K1C. Renal IL-11 expression was elevated in 2K1C. In the heart there was only a trend toward higher IL-11 expression in 2K1C. IL-11 in the kidney in 2K1C correlated with the expression of transforming growth factor (TGF)-β1/2, collagens, fibronectin, osteopontin, as well as tissue inhibitors of metalloprotease 1/2. There were also correlations of IL-11 with tissue collagen expansion, number of activated fibroblasts and serum creatinine, but no correlation with mean arterial pressure. Renal expression of IL-11 was highest in rats with malignant hypertension. CONCLUSIONS: Renal IL-11 expression of renovascular hypertensive rats is markedly increased and correlates with profibrotic markers and loss of function and might therefore serve as a biomarker for the severity of hypertensive nephrosclerosis.
CRIS-Team Scopus Importer:2020-04-14
Keywords: blood pressure; hypertension; interleukin-11 (IL-11); malignant hypertension; renal fibrosis; two-kidney one-clip renovascular hypertension (2K1C)

No benefit of HIF prolyl hydroxylase inhibition for hypertensive renal damage in renovascular hypertensive rats - Hartner, Andrea; Dambietz, Thomas; Cordasic, Nada; Willam, Carsten; Burzlaff, Nicolai; Brötsch, Martin; Daniel, Christoph; Schiffer, Mario; Amann, Kerstin Ute; Veelken, Roland; Schley, Gunnar; Hilgers, Karl Friedrich (Frontiers in Physiology, 2023)
Introduction: We previously reported that malignant hypertension is associated with impaired capillary density of target organs. Here, we tested the hypothesis that stabilization of hypoxia-inducible factor (HIF) in a modified “preconditioning” approach prevents the development of malignant hypertension. To stabilize HIF, we employed pharmacological inhibition of HIF prolyl hydroxylases (PHD), that profoundly affect HIF metabolism. Methods: Two-kidney, one-clip renovascular hypertension (2K1C) was induced in rats; controls were sham operated. 2K1C rats received either intermittent injections of the PHD inhibitor ICA (2-(1-chloro-4-hydroxyisoquinoline-3-carboxamido) acetate) or placebo. Thirty-five days after clipping, the frequency of malignant hypertension was assessed (based on weight loss and the occurrence of characteristic vascular lesions). In addition, kidney injury was compared between all ICA treated versus all placebo treated 2K1C, regardless of the occurrence of malignant hypertension. HIF stabilization was evaluated by immunohistochemistry, and HIF target gene expression by RT-PCR. Results: Blood pressure was elevated to the same degree in ICA- and placebo-treated 2K1C compared to control rats. ICA treatment did not affect the frequency of malignant hypertension or the extent of kidney tissue fibrosis, inflammation, or capillary density. There was a trend towards higher mortality and worse kidney function in ICA-treated 2K1C rats. ICA increased the number of HIF-1α-positive renal tubular cell nuclei and induced several HIF-1 target genes. In contrast, expression of HIF-2α protein as well as HIF-2 target genes were markedly enhanced by 2K1C hypertension, irrespective of ICA treatment. Discussion: We conclude that intermittent PHD inhibition did not ameliorate severe renovascular hypertension in rats. We speculate that the unexpected strong renal accumulation of HIF-2α in renovascular hypertension, which could not be further augmented by ICA, may contribute to the lack of a benefit from PHD inhibition.
CRIS-Team Scopus Importer:2023-07-21
Keywords: capillarization; HIF stabilization; malignant hypertension; renovascular; vascular lesions